The Effect of Monopoly Learning Media on the Science Learning Outcomes of Third Grade Students at Public Elementary School 091436 - Diah Mareta Damanik; Emelda Thesalonika; Lisbet Novianti Sihombing (Ludi Litterarri, 2025)
This study aims to analyze the effect of the Monopoly Learning Media on the learning outcomes of third-grade students at SD Negeri 091436 Tambun Raya in the topic “Energy Around Us.” The research was motivated by the low achievement in IPAS learning and the dominance of teacher-centered instruction that limited student engagement. A quantitative approach using a One Group Pretest–Posttest design was employed. The sample consisted of 20 third-grade students selected through total sampling. The instrument was a 20-item multiple-choice test that had been validated for its validity, reliability, discrimination index, and difficulty level. Data were analyzed using a paired sample t-test. The findings reveal an increase in the mean score from 56.75 (pretest) to 84.75 (posttest), with a gain of 28 points. The t-test results indicate that tcalculated > ttable, confirming that the monopoly media has a significant effect on learning outcomes. Observations also show improvements in students’ motivation, engagement, and social interaction during game-based activities. These findings demonstrate that monopoly media is effective for IPAS learning, particularly for abstract concepts. The study recommends the broader use of educational game media to enhance conceptual understanding and student participation.